Solid-state protein formulations. (January 2015) - Angkawinitwong, Ukrit; Sharma, Garima; Khaw, Peng T; Brocchini, Steve; Williams, Gareth R
When formulated as liquid dosage forms, therapeutic proteins and peptides often show instability during handling as a result of chemical degradation. Solid formulations are frequently required to maintain protein stability during storage, transport and upon administration. Herein we highlight current strategies used to formulate pharmaceutical proteins in the solid form. An overview of the physical instabilities which can arise with proteins is first described. The key solidification techniques of crystallization, freeze-drying and particle forming technologies are then discussed. Examples of current commercial products that are formulated in the solid state are provided and include neutral protamine Hagedorn – insulin crystal suspensions, freeze-dried monoclonal antibodies and leuproride polylactide-co-glycolide microparticles. Finally, future perspectives in solid-state protein formulation are described.